Phytochemical Profile and Antioxidant Activity of Bajakah Kalalawit Leaf Extract - Priyadi, Muhammad; Gunawan, Yohanes Edy; Saputra, Rizki Rachmad; Decenly, Decenly; Citrariana, Shesanthi (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
Natural products have long been recognized for their significant role in supporting human health, with natural ingredients playing an essential part in disease treatment and wellness across generations. The bajakah species, particularly bajakah kalalawit (Uncaria gambir Roxb.), has gained attention in recent research due to its potential bioactive compounds. Especially, its antioxidant properties from any part of plant has potential to explore. This study aims to determine the various secondary metabolite compounds possessed by bajakah kalalawit leaves and test their antioxidants. Bajakah kalalawit leaves were extracted using reflux with aqueous solvents, checked for phytochemical profiles using GC-MS, and conducted antioxidant tests using the DPPH method. Based on the phytochemical test, there are 22 predicted compounds in the extract and the antioxidant test results showed an IC50 value of 14.44 ppm. In conclusion, bajakah kalalawit leaf aqueous extract has antioxidant activity and is supported by bioactive compounds.